Institucionalização de políticas LGBTs : um estudo sobre a criação do tripé da cidadania LGBT no município de São Carlos entre os anos de 2009 e 2012 - Vergili, Guilherme Efraim (2016)
From the mid-1990s the development of public policies for the LGBT segment gained prominence in Brazil, adopting a promotional bias of human rights (Carmona, Prado, 2009; Carrara, 2010). But it was at the end of the next decade with the holding of conferences and the establishment of a "tripod of citizenship" (consisting of a council, an agency in the executive branch and a policy plan) in the federal government that the institutionalization of these policies was strengthened by the other federative entities. The municipality of São Carlos is characterized as being one of the first cities in São Paulo state to adopt public policies aimed at the LGBT segment through the interaction of governmental and the organized group "ONG Visibilidade LGBT". Thus, we intend to analyze the formulation of sexual diversity policy proposed and developed by the City of São Carlos, between the years 2008 and 2012, through the research on the process of entry of this issue on the government agenda. Through the validation of the Multiple Streams framework, developed by John Kingdon (1995 [2003]), which analyzes qualitatively the process of schedule training and the actions proposed by the government to deal with them, it is intended so with the political science literature bring light on the issue of sexual diversity develops as government policy at the municipal level.